2020
DOI: 10.1111/ggi.14033
|View full text |Cite
|
Sign up to set email alerts
|

Social support among older adults in Malaysia

Abstract: Aim This study aimed to determine the factors that influence perceived social support among older adults in Malaysia. Methods We used the 11‐item Duke Social Support Index to assess perceived social support through a face‐to‐face interview. Higher scores indicate better social support. Linear regression analysis was carried out to determine the factors that influence perceived social support by adapting the conceptual model of social support determinants and its impact on health. Results A total of 3959 respon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 17 publications
2
12
0
Order By: Relevance
“…A total of 39 articles describing 34 studies with 59,944 participants from six ASEAN countries were included in the review (Figure 1) as data from three cohorts were reported in several publications. (12)(13)(14)(15)(16)(17)(18)(19) Twenty-five studies were included in the meta-analysis. (14,17,18,)…”
Section: Resultsmentioning
confidence: 99%
“…A total of 39 articles describing 34 studies with 59,944 participants from six ASEAN countries were included in the review (Figure 1) as data from three cohorts were reported in several publications. (12)(13)(14)(15)(16)(17)(18)(19) Twenty-five studies were included in the meta-analysis. (14,17,18,)…”
Section: Resultsmentioning
confidence: 99%
“…The presence of loved ones (such as a spouse or children) with older adults plays an important role in maintaining good mental health [115]. Numerous studies have confirmed that older men receive more support from their wives and report greater satisfaction [116,117]; more-over, older women receive feelings of well-being when they receive support from children or friends [118].…”
Section: Discussionmentioning
confidence: 99%
“…The reason may be that the elderly have more time and energy to communicate with their friends and family after retirement, express their feelings, and get responses from others, thereby increasing their social support. Most older adults in Malaysia also perceive a higher level of social support [47]. However, in a study of Mexico, social support was found to be lower among older adults [48].…”
Section: Discussionmentioning
confidence: 99%